Istota władzy gospodarczej producentów w świetle ogólnej teorii władzy - Trojanek, Jacek (Wydział Prawa i Administracji UAM, 1986)
The implementation of the Polish economic reform occurs in the extremely unfavorable market conditions. The internal market is not only unbalanced but also dominated by monopolistic structures. The unbalanced and closed market becomes a source of the strong market power of those enterprises which supply determined goods and services. The present article is the author's attempt at theoretical explication of the essence of economic power of producers and the discussion of the characteristic features of that notion against the background of the general theory of power. In the first part of the article the author reviews definitions of the general notion of power encountered by him in the modern Western and socialist sociological, politological and legal literature. The definitions are of a certain value as they can facilitate understanding the essence and recognition of the action mechanisms of that specific sort of power, being the economic power of the socialized producers. The second part of the article brings about the author's discussion of the essence of the economic power of producers in the socialized economy. The authors shares opinions of those Polish economists, according to whom the notion of economic power can be referred to situations at which an enterprise gains a considerable market advantage, over other subjects, what allows it to shape regulational horizontal links according to the own rules of a game (independently from the official findings) as well as exercise influence over regulational vertical links (with the administrative center) to reach its own goals, contradicting the social goals and the goals of other market subjects. Next the author discusses the most important features of the economic power of the producers. The analysis produced in this respect resulted in formulating the following conclusions: — the economic power of the producers is a social relation; — the relation is not grounded in the legal regulation, it is effected by the factual position of a given enterprise on the market; — the economic power reveals an authoritarian character, power relations are this asymmetrical (there are dominating and dominated subjects in them); — the obedience is a substantial element of the economic power, the excèssiveness and range of power can be proved by a number of acts of the obedience and by a number of subjects manifesting it; — economic organizations as users of power are vested with a peculiar extra- -legal imperium, having the means of economic duress at their disposal; — two types of economic power are to be distinguished: the potential power and the power excercised; as the power being a certain potential, chance or possibility may, but does not have to be realized; — the economic power of the producers is neither forced nor absolute; there are possibilities to control it, limit it or eliminate it; — the economic power is transitive and relative as an enterprise is related to specific elements of its milieu both by means of dominance and subjection.
The Essence of Economic Power of Producers in the Light of the General Theory of Power